WORK - LIFE INTEGRATION POLA KERJA BARU PEMICU KELELAHAN KERJA: ADAPTASI BARU PADA MASA PANDEMI COVID – 19 - Meida Rachmawati; Ignatius Hari Santoso (Jurnal Manajemen, 2021)
This study aims to examine the effect of work life integration as a new phenomenon in the middle of Covid outbreak in Indonesia toward work exhaustion , and the mediating effect of work life balance. 100 samples recruited in this researh is came from workers with at least two year working experience since Covid outbreak. Data is done with an open-ended questionnaire, which processed by Smart PLS 3.0. The results of the study show that work life integration and work life balance have significant effect toward work exhaustion. Besides, work life balance is partially mediate between work life integration and work exhaustion. As the practical implication we suggest that employee should build priority activities to prevent two or more activities executed at the same time.